Analysis of Time Comparison and Costs of Implementing Road Implementation with Time Cost Trade-Off Method - Shintia Wulandari, Evita; Piadi, Koes; Restuti Wulandari, Diah Ayu (Malikussaleh University, Aceh, Indonesia, 2021)
Project for the construction of the Gunungsari Banjar Sugihan - Kandangan diversion channel, Surabaya, in the implementation of this project there was a delay in how many works. One way to anticipate this delay is by accelerating it using the Time Cost Tread Off method, through alternative working hours (overtime) and additional labor. The method is used so that the project can run smoothly and so that the project can be accelerated in completion. Time-Cost Trade-Off analysis, better known as TCTO. jobs included in the critical cross and jobs that are not allowed to delay are as follows: Urugan Sirtu (solid), Lean concrete fc 10 Mpa work, Rigid pavement fc 30 Mpa work finishing growing, iron beginning work.